THE EFFECT OF TRADITIONAL AND ELECTRONIC WORD-OF-MOUTH ON PURCHASE DECISION - Sanger, Chintya Amelia Nelly (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2013)
Word-of-mouth (WOM) Marketing is widely considered the most influential source of information for consumer purchase decisions, and the explosion of social media has stirred interest in the communication.The relation of Traditional Word-of-Mouth and electronic word-of-mouth ( e-wom ) on purchase decision are positively influential. Research to 100 respondents of student in International Business Administration program, Economic and Business faculty in SamRatulangi university. The most of student knows about word-of-mouth of marketing. Based on the result of this research conducted to analyze the effect of Traditional word-of-mouth and electronic word-of-mouth on purchase decision with study case at International Business Administration (IBA)’s student, it can be inferred that. The result of regression analysis indicates that the job characteristic and working condition have a significant effect to purchase decision in student of IBA.WOM marketing has positively effect on purchase decision, they chose to buy a goods or services based on recommendation from family, close relatives, or friends. In research showed that the process of  WOM much going on with  Face-to-face recomendation or called Traditional Word-of-Mouth, rather than  electronic media. Keywords : purchase decision, word-of-mouth marketing